Rapid assessment of Hib disease burden in Vietnam - Slack Mary PE; Rani Manju; Mai Trinh; Nguyen Hien; Dang Duc; Nyambat Batmunkh; Kilgore Paul E (BMC, 2011)
Abstract Background Several countries have applied the Haemophilus influenzae type b (Hib) rapid assessment tool (RAT) to estimate the burden of Hib disease where resources for hospital- or population-based surveillance are limited. In Vietnam, we used the Hib RAT to estimate the burden of Hib pneumonia and meningitis prior to Hib vaccine introduction. Methods Laboratory, hospitalization and mortality data were collected for the period January 2004 through December 2005 from five representative hospitals. Based on the WHO Hib RAT protocol, standardized MS Excel spreadsheets were completed to generate meningitis and pneumonia case and death figures. Results We found 35 to 77 Hib meningitis deaths and 441 to 957 Hib pneumonia deaths among children < 5 years of age annually in Vietnam. Overall, the incidence of Hib meningitis was estimated at 18/100,000 (95% confidence interval, CI, 15.1-21.6). The estimated Hib meningitis incidence in children < 5 years age was higher in Ho Chi Minh City (22.5/100,000 [95% CI, 18.4-27.5]) compared to Hanoi (9.8/100,000 [95% CI, 6.5-14.8]). The Hib RAT suggests that there are a total of 883 to 1,915 cases of Hib meningitis and 4,414 to 9,574 cases of Hib pneumonia per year in Vietnam. Conclusions In Hanoi, the estimated incidence of Hib meningitis for children < 5 years of age was similar to that described in previous population-based studies of Hib meningitis conducted from 1999 through 2002. Results from the Hib RAT suggest that there is a substantial, yet unmeasured, disease burden associated with Hib pneumonia in Vietnamese children.